2020
DOI: 10.1371/journal.pone.0236624
|View full text |Cite
|
Sign up to set email alerts
|

Pain during pars plana vitrectomy following sub-Tenon versus peribulbar anesthesia: A randomized trial

Abstract: Purpose To compare pain during pars plana vitrectomy (PPV) following topical lidocaine jelly and sub-Tenon anesthesia versus peribulbar anesthesia. Methods Prospective, single-center, randomized study. Patients scheduled for PPV for macular hole (MH) or epiretinal membrane (ERM) at the Retina and Vitreous Section of the Department of Ophthalmology, Ribeirão Preto Medical School, University of São Paulo were randomly assigned to one of two groups in a 1:1 allocation rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 56 publications
0
19
2
Order By: Relevance
“…We also analyzed the possibility of coincidence between the two most common comorbidities of patients undergoing vitreoretinal surgeries, arterial hypertension and DM, in relation to the incidence of PONV [43][44][45]. Diabetic patients benefit from enhanced vision and improved lifestyle from the introduction of vitreoretinal surgeries [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also analyzed the possibility of coincidence between the two most common comorbidities of patients undergoing vitreoretinal surgeries, arterial hypertension and DM, in relation to the incidence of PONV [43][44][45]. Diabetic patients benefit from enhanced vision and improved lifestyle from the introduction of vitreoretinal surgeries [46].…”
Section: Discussionmentioning
confidence: 99%
“…First, all patients received a fixed volume of crystalloids (10 mL/kg of body weight) to balance the overnight fluid loss, which was estimated to be approximately 40 mL/hour. Intraoperatively, when the depth of anesthesia using spectral entropy EEG (SE) was fixed at [40][41][42][43][44][45] in all patients and the IRNA was kept under SPI guidance levels (in accordance with AoA regimen), the use of anesthetic agents had a presumably similar impact on the intraoperative fluid requirement in individual patients, despite the group allocation. We hypothesize that the intraoperative monitoring of the depth of anesthesia using SE and analgesia using SPI could have created comparable conditions for all patients to direct fluid challenge according to their needs based on the intraoperative hemodynamic changes in response to the anesthetic regimen required to perform PPV.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to ensure that a sufficient amount of anesthetic reaches the retrobulbar space, peribulbar anesthesia requires a larger volume of anesthetic (up to 10 ml) with or without hylase to help spread the anesthetic [28][29][30]. Moreover, a randomized trial from 2020 comparing sub-Tenon's anesthesia (2-4 ml ropivacaine) and peribulbar anesthesia (4-6 ml ropivacaine) for PPV showed that sub-Tenon's anesthesia was more effective in controlling pain during the whole vitrectomy procedure than peribulbar anesthesia [24]. To date, there were few comparative clinical studies on the trans-sub-Tenon's ciliary nerve block anesthesia and transcutaneous retrobulbar anesthesia for vitreoretinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria: (1) history of previous vitreoretinal surgery; (2) history of ocular trauma; (3) the patient could not cooperate with the operation; (4) the patient was allergic to ropivacaine or any of its components or similar drugs; (5) the patient was pregnant or lactating female. The sample size was calculated based on previous literature review [13,17,24]. The estimated sample size was 120 patients (60 in each group) based on type I error (α) of 5%, and a power (1-β) of 90%.…”
Section: Methodsmentioning
confidence: 99%
“…The newly introduced drug, i.e., ropivacaine, has a more specific effect on the motor nerve fibers [5][6][7] . Furthermore, this drug has lesser cardiac toxicity 8 . On the other hand, bupivacaine possesses a faster onset and regression of sensory and motor blocks.…”
Section: Introductionmentioning
confidence: 99%